Environmentally friendly Rb3V5O14 fluorescent red pigment. (January 2017) - Kim, Sun Woog; Hasegawa, Takuya; Watanabe, Mizuki; Sugimoto, Kazuma; Saito, Yu; Uematsu, Kazuyoshi; Toda, Kenji; Sato, Mineo
Abstract: Rb3 V5 O14, which was successfully synthesized by a water assisted solid state reaction (WASSR) method, is a fluorescent red pigment that is environmentally friendly. The Rb3 V5 O14 fluorescent pigment showed a strong optical absorption in the green light region due to the energy transfer from O 2− 2p orbital to V 5+ 3d orbital of VO5 polyhedra and band-gap energy of Rb3 V5 O14 was 2.02 eV. The fluorescent pigment presented a broad red emission peaked at 625 nm due to the 3 T2  →  1 A1 and 3 T1  →  1 A1 transitions of the [VO4 ] 3− group. The Rb3 V5 O14 fluorescent pigment showed a bright-vivid red body color, and the L *, a *, and b * values were 47.4,  +45.9, and +34.4, respectively. Highlights: Nontoxic fluorescent red pigment Rb3 V5 O14 was synthesized by WASSR method. Rb3 V5 O14 exhibited a broad red emission with a peak at 625 nm. The fluorescent pigment has a strong optical absorption band in the green light region. The fluorescent pigment obtained in this study shows the bright-vivid red body color. The Rb3 V5 O14 fluorescent red pigment is expected for application as the color cosmetics.